Global research trends of digital applications in medical education - Bingxin Chen; Xiuli Zhang (Medicine, 2026)
Background: The integration of digital applications into medical education has transformed traditional pedagogical approaches by offering innovative solutions for knowledge and skill acquisition. Given the profound impact of digital applications, this study employed bibliometric analysis to map global trends, identify key contributors, and delineate emerging themes in digital applications in medical education. Methods: We identified 2096 articles published from January 1, 2014, to December 31, 2024, from the Web of Science Core Collection. Using Microsoft Office Excel (Microsoft Corp.) and VOSviewer 1.6.19, we visualized annual publication trends, countries, organizations, journals, authors, and keywords. Results: From January 1, 2014, to December 31, 2024, annual publications surged from 85 to 448 articles. The United States of America dominated contributions, with the most publications (732 documents) and the most citations (12,525). Cooperation among organizations was characterized by partnerships between universities and hospitals, with the University of Toronto as the most prolific contributor (48 documents and 1659 citations). BMC Medical Education (117 documents and 1598 citations) and Anatomical Sciences Education (51 documents and 1827 citations) displayed high publication volumes and prominent citations. Konge Lars published the most documents, totaling 51, and led research on digital applications in medical education with 1141 citations. The keywords mainly focused on medical education, virtual reality, and simulation. Conclusions: This study collected articles from the past decade and revealed key contributors and global trends. The findings could help researchers and medical educators identify potential collaborators and provide direction for future research.